Assessment of self-medication practices and safety profile of medicines utilisation among pregnant women attending antenatal clinics in Freetown, Sierra Leone: a multicentre cross-sectional study - Onome Thomas Abiri; Shakiratu Lawal; Joshua Coker; James Baligeh Walter Russell; Ibrahim Franklyn Kamara; N'falie Ibrahim Sesay; Joseph Sam Kanu; Foday Umaro Turay; Michael Lahai; Henry Edward Clarence Carter; Mohamed Bawoh; Mohamed Samai (Taylor & Francis Group, 2024)
Background Despite the potential foetal and maternal risks of self-medication, studies on self-medication practice and the safety profile of medicines used during pregnancy are scarce in our setting. This study determined the self-medication practice and safety profile of medicines used among pregnant women.Methods This cross-sectional study was conducted in face-to-face interviews among 345 pregnant women at three hospitals in Sierra Leone. Data were analysed using descriptive statistics and binary logistic regression to determine the prevalence and associated factors of self-medication.Results A total of 345 pregnant women participated in the study. The prevalence of self-medication prevalence among pregnant women with conventional and/or herbal medicine was 132 (38.3%). Also, 93 (75%) of the conventional medicines (CMs) were categorised as probably safe, of which paracetamol 36 (29.0%) was commonly used, followed by amoxicillin 23 (18.5%) and antimalarials 22 (17.7%) for common illnesses such as headache 30 (25.4%), urinary tract infection 23 (19.4%) and malaria 22 (18.6%). The most common reason for self-medication was previous experience with the disease 24 (27.3%). Luffa acutangula 19 (30.2%) was the most used herbal medicine (HM), and Oedema 30 (47.6%) was the most reported ailment. Among the HM users, 34 (54.0%) believe they are more effective than CMs. Secondary school education (AOR = 2.128, 95%CI = 1.191-3.804, p = 0.011), tertiary education (AOR = 2.915, 95%CI = 1.104-7.693, p = 0.031), monthly income of greater than NLe 1,000 (AOR = 4.084, 95% CI = 1.269-13.144, p = 0.018), and perceived maternal illness (AOR = 0.367, CI = 0.213-0.632, p = <0.001) were predictors of self-medication.Conclusion Self-medication practice was highly prevalent and was associated with educational status, monthly income, and perceived maternal illness during pregnancy. Therefore, intervention programmes should be designed and implemented to minimise the practice and risk associated with self-medication among pregnant women.